An exploratory study on determining motivations, constraints, and strategies for coping with constraints to participate in outdoor recreation activities: Generation Z - Yenal Yağmur; Altan Demirel (Journal of Tourism, Heritage & Services Marketing)
Purpose: The present study aimed to investigate the behaviors and preferences of university student-generation Z members towards outdoor activities based on the theory of leisure constraints.